Transgenic wheat with increased endosperm lipid – Impacts on grain composition and baking quality. (September 2021) - Larkin, P.J.; Liu, Q.; Vanhercke, T.; Zhou, X.R.; Bose, U.; Broadbent, J.A.; Colgrave, M.L.; Ral, J.P.; Reynolds, K.B.; Sun, M.; El Tahchy, A.; Shrestha, P.; et al.
Abstract: The impact of endogenous lipids on baking remains elusive and sometimes contradictory. Previous studies heavily relied on relatively small varietal or environmental differences, lipase treatments, or defatting and reconstitution treatments. While there is a general literature consensus that removing or modifying triacylglycerides (TAG) to more polar forms is desirable, this conclusion is challenged by the fact that bakeries add lipids, predominantly TAG, during processing. We have set out to test the impact of elevated levels of TAG when produced endogenously in starchy endosperm in transgenic wheat. Transgenic genotypes were produced with the introduction of three genes: endosperm-specific promoters driving maize Wrinkled1a, Arabidopsis DGAT1, and sesame oleosin . The resulting wheat lines have consistently produced grain with a substantive increase of TAG levels, up to 8-fold, in the endosperm over five generations, including two seasons in the field. No change in polar lipid content was observed. Lipid droplets were readily visualised and evident throughout the starchy endosperm. We have studied the increase in TAG and changes to fatty acid profile throughout grain development. Compared to control seed, the high oil wheat had a shift to oleic acid at the expense of polyunsaturated fatty acids. While seedling growth or grain yield were not significantly diminished in the field, average individual seed weight and diameter were slightly reduced. No significant changes could be shown in the content of starch, resistant starch, protein, or beta-glucan in field-grown wholemeal flours; however, there was an increase in α-amylase 1 and free glucose. Small-scale baking of field-grown flours showed a small decrease in bread loaf volume, but no significant change in biscuit diameter or height. Graphical abstract: Image 1 Highlights: Introducing 3 transgenes to wheat achieved 8-fold increase in endosperm TAG. Little impact on grain size, growth or yield in field plots. No significant changes to starch or protein content. A surprising induction in α-amylase 1. A small decrease in bread loaf volume, but no significant change in biscuit size.